Using co‐design to adapt the care partner hospital assessment tool for dementia - Beth Fields; Benazir Meera; Kathryn Istvanek; Te‐Lien Ku; Hanna J. Barton; Chloe Muntefering; Nicole E. Werner (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring)
Abstract INTRODUCTION Care partners play a critical role in supporting hospitalized individuals with dementia. The Care Partner Hospital Assessment Tool (CHAT) is a standardized tool for identifying and training care partners, but has not been adapted for dementia care. This study aimed to modify CHAT for this population. METHODS Using co‐design methodology, two parallel design teams—consisting of seven clinicians and five dementia care partners—suggested adaptations and shared satisfaction with the tool. RESULTS Thematic analysis revealed three themes informing adaptation of CHAT to Dementia Care Partner Hospital Assessment Tool (D‐CHAT): (1) identifying and documenting power of attorney, (2) recognizing care partner tasks and responsibilities, and (3) providing dementia‐specific educational resources. Participants expressed high satisfaction with the final D‐CHAT. DISCUSSION D‐CHAT represents a pioneering effort co‐designed by care partners and clinicians to enhance hospital caregiving assessments for dementia care. CLINICAL TRIAL NUMBER: NCT05592366 Highlights The Dementia Care Partner Hospital Assessment Tool (D‐CHAT) was created using a parallel co‐design approach with key informants — clinicians and care partners. D‐CHAT can help care partners and clinicians identify power of attorney early, recognize caregiving responsibilities, and provide dementia‐specific resources. D‐CHAT was described as ‘empowering,’ ‘comprehensive,’ ‘collaborative,’ and ‘helpful.’